2019
DOI: 10.3390/cancers11122021
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor of DNA-Binding Protein 4 Suppresses Cancer Metastasis through the Regulation of Epithelial Mesenchymal Transition in Lung Adenocarcinoma

Abstract: Metastasis is a predominant cause of cancer death and the major challenge in treating lung adenocarcinoma (LADC). Therefore, exploring new metastasis-related genes and their action mechanisms may provide new insights for developing a new combative approach to treat lung cancer. Previously, our research team discovered that the expression of the inhibitor of DNA binding 4 (Id4) was inversely related to cell invasiveness in LADC cells by cDNA microarray screening. However, the functional role of Id4 and its mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…A wealth of evidence suggests that epithelial-mesenchymal transition (EMT) plays pivotal roles in migration and metastasis of tumor cells. [4][5][6] Transforming growth factor-β (TGF-β) is major inducer of EMT, which is known to be expressed in most adenocarcinomas including LUAD and associates with cancer cell metastasis. [7][8][9][10] Long noncoding RNAs (lncRNAs) are defined as transcripts of length > 200 nucleotides with a low coding potential.…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of evidence suggests that epithelial-mesenchymal transition (EMT) plays pivotal roles in migration and metastasis of tumor cells. [4][5][6] Transforming growth factor-β (TGF-β) is major inducer of EMT, which is known to be expressed in most adenocarcinomas including LUAD and associates with cancer cell metastasis. [7][8][9][10] Long noncoding RNAs (lncRNAs) are defined as transcripts of length > 200 nucleotides with a low coding potential.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, 2 h coriloxin treatment also reduced the CL1-5 cells’ p-AKT levels. Aware that the epithelial–mesenchymal transition (EMT) contributes critically to cancer cell metastasis [ 19 ], we examined the levels of EMT-related markers in the cells. Coriloxin dose-dependently lowered the levels of vimentin and N-cad, which are mesenchymal markers ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…Id1 opposed twist activity, thus promoting cell metastasis to the lung via EMT [23]. It has been indicated that Id4 can inhibit lung cancer metastasis and mesenchymal-epithelial transition (MET) by binding to slug and promoting E-cadherin expression [24]. MMPs are also important markers of EMT and play a major role in the biological behaviours of cells such as cell proliferation, migration, and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Id proteins dimerize with bHLH protein, which inhibits their DNA binding activity [28]. In the lung cancer, Id4 binds to slug, which interferes with its interaction with E-box promoter, and then suppresses the metastasis of cancer cells [24]. Id4 interacts with MDC1 and other DNA repair proteins which govern the DNA damage response [29].…”
Section: Discussionmentioning
confidence: 99%